Online interpersonal trust and online altruistic behavior in college students: the chain mediating role of moral identity and online social support - Sun, Daokai; Lin, Yingying; Liao, Chuanjing; Pan, Lili (Frontiers in Psychology, 2024)
Background: The prevalence of online altruistic behaviors among the college students has attracted widespread attention. However, the factors influencing this are still unclear. The objective of this study was to explore the relationship and mechanism of online interpersonal trust, moral identity, online social support and online altruistic behavior among college students. Methods: The survey was conducted among 986 Chinese college students using The Interpersonal Trust Scale for the Internet,Moral Identity Scale ,The Internet Social Support Questionnaire for College Students and The Internet Altruistic Behavior Questionnaire for College Students. Results: Moral identity, online social support, online interpersonal trust and online altruistic behavior were significantly positively correlated (r=0.09-0.39, p<0.01). Online social support plays a partial mediating role in the relation between online interpersonal trust and online altruistic behavior, accounting for 33.76% of the total effect, while moral identity and online social support play a chain mediating role in the relation between online interpersonal trust and online altruistic behavior, accounting for 2.23% of the total effect. Conclusion: Online interpersonal trust not only directly affects college students’ online altruistic behavior, but also indirectly influences it through moral identity and online social support.